Performance Of Pure Danish Holstein Friesian Bulls Under Indian Management And Tropical Climatic Conditions - Tiwari, Ritesh; Mishra, G. K.; Singh, R. B; Saxena , S. K.; Siddiqui , M. U. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Data on 1798 ejaculates obtained from three high pedigree pure Danish Holstein Friesian bulls were analyzed to observe the influence of Indian management and tropical climatic conditions on various seminal characteristics. The effect of seasons was significant (P
Keywords: Danish Holstein Friesian bulls; Indian management; semen ejaculates